2015
DOI: 10.1002/hyp.10468
|View full text |Cite
|
Sign up to set email alerts
|

Preferential flow mechanisms identified from staining experiments in forested hillslopes

Abstract: Abstract:Field staining experiments in five different plots at two sites in Japan (Okaya in Nagano Prefecture and Konohara in Mie Prefecture) were undertaken to improve understanding of subsurface stormflow runoff within organic layers of natural forested hillslopes. This type of shallow lateral subsurface flow, specifically referred to as biomat flow, was observed only at the Okaya site based on staining experiments conducted under controlled water application rates. When the same irrigation rate (50-100 mm h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 59 publications
(126 reference statements)
2
41
0
Order By: Relevance
“…This is confirmed by the (visual) observation of lateral translocations of tracer solution along the hillslope in the upper soil during excavation of the soil pits. The high importance of lateral subsurface flow in the O-layer and adjacent mineral soil, known as biomat flow (Sidle et al, 2007), was shown recently by Gerke et al (2015) for forested hillslopes in Japan. They divided two key flow mechanisms:…”
Section: Dye Distribution and Flow Patternsmentioning
confidence: 96%
“…This is confirmed by the (visual) observation of lateral translocations of tracer solution along the hillslope in the upper soil during excavation of the soil pits. The high importance of lateral subsurface flow in the O-layer and adjacent mineral soil, known as biomat flow (Sidle et al, 2007), was shown recently by Gerke et al (2015) for forested hillslopes in Japan. They divided two key flow mechanisms:…”
Section: Dye Distribution and Flow Patternsmentioning
confidence: 96%
“…The preferential flow fraction, PF-fr, is the fraction of the total infiltration that flows through preferential flow paths [48]. The calculation method for the PF-fr was widely used in previous studies that only relied on the UniID as the boundary between the matrix flow area and the priority flow area [20,21,26,48,49]. However, the traditional calculation can lead to the inability to truly and completely distinguish the priority flow from the matrix flow.…”
Section: Preferential Flow Indicesmentioning
confidence: 99%
“…CC BY 4.0 License. for laboratory measurements on pore scale are: (i) change of the sample's microstructure and therefore its physical properties through cracking and self-filtration (Zeinijahromi et al, 2016;Dikinya et al, 2008) (ii) pressure changes due to the influence of wall effects (Ferland et al, 1996) and finally (iii) difficulties to measure on irregular grain shapes and small grain sizes of the porous medium (Cui et al, 2009;Gerke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%